Desenvolvimento, caracterização e avaliação da atividade antitumoral do extrato hidroetanólico de Passiflora alata curtis encapsulado em lipossomas híbridos - Araujo, Sabrina Mendes Silva (2020)
Development, characterization and evaluation of the antitumor activity of the hydroethanolic extract of Passiflora alata Curtis encapsulated in hybrid liposomes, Sabrina Mendes Silva Araujo, Federal University of Sergipe, São Cristóvão, 2020. Cancer is one of the most feared diseases of recent years and is progressing progressively in the 21st century. It is a multifactorial disease characterized by genetic mutations and epigenetic changes, which can be triggered by environmental and behavioral factors related to lifestyle. Currently, several antitumor nanodrugs are being tested in clinical and pre-clinical trials and show promise in terms of therapy and diagnosis. This work aimed to develop biotechnologically and evaluate the effect of the hydroethanolic extract of the leaves of Passiflora alata Curtis encapsulated in hybrid liposomes (LHPA) on the cytotoxic activity in vivo, in animals with sarcoma 180. P. alata was submitted to extraction, and encapsulated in unilamer liposomes. The nanoparticles were characterized in terms of size, polydispersity index and surface charge (zeta potential) by dynamic light scattering. The morphology of the particles obtained was analyzed by scanning electron microscopy (SEM). The in vivo antitumor activity of (LHPA) was evaluated using Swiss mice transplanted with sarcoma tumor 180 (S180) (2 x 106 cells / 0.5 mL / mouse), subcutaneously. To evaluate the effect of LHPA on tumor growth, one day after tumor inoculation, treatment was instituted for 7 consecutive days, intraperitoneally (i.p.) and orally, in different experiments. One day after the end of the treatment, the animals were euthanized, and then the peripheral blood was collected, with subsequent resection of the organs and tumors to measure the tumor growth (% inhibition), later laboratory analyzes (hematological and biochemical). The averages were obtained from data with Gaussian distribution, and were compared with each other through analysis of variance (ANOVA), followed by Tukey's multiple comparison test (p <0.05. It was observed that the LHPA, after administration via ip, inhibited tumor growth by 68.08 and 83.44% at doses of 50 and 100 mg / kg / day, respectively, the negative control group (vehicle) had inhibition equal to 0, the chemotherapeutic 5-fluorouracil was used as a positive control in this testing phase.The evaluation of antitumor activity after oral administration showed that LHPA at doses of 100 and 200 mg / kg / day showed a percentage of inhibition of 55.15 and 65.85%, in this order, negative control showed inhibition equal to 0, cyclophosphamide was used as positive control, so the LHPA nanoparticles showed significant values of tumor inhibition by different routes of administration tested.